Effect of calcium, magnesium, sodium and potassium levels in seminal plasma of Holstein bulls on spermatological characters - Gür, S; Demirci, E (Scientific Technical Research Council Turkey, 2000)
This study was conducted to investigate the levels calcium, magnesium, sodium and potassium in the seminal plasma of bulls, semen volume, sperm motility, sperm concentration and the correlation between these parametres. Five Holstein bulls constituted the material of this study. Twenty ejaculates were collected from each bull and the spermatological characteristics of these ejaculates were determined. Then, seminal plasma was separated from 3ml semen from each ejaculate by centrifugation at 1500g for 20 min at 4 degrees C. Calcium, magnesium, sodium and potassium concentrations in seminal plasma were determined by atomic absorption spectrophotometry. The average values for calcium, magnesium, sodium and potassium in the sample of seminal plasma were 40.22 +/- 1.35. 6.32 +/- 0.86, 266.60 +/- 34.83 and 154.08 +/- 26.48 mg/100 mi respectively. The average values for semen volume, sperm motility and sperm concentration were 4.42 +/- 0.52 mi, 75.5 % and 1.03 +/- 0.10 x 10(9)/ mi respectively. The analysis of variance indicated that there were no significant differences in the levels of sperm concentration and motility among the bulls. However, calcium, magnesium, sodium, potassium levels and semen volume differed significantly among the bulls. The calcium content of seminal plasma was positively correlated with sodium and sperm concentration. The sodium content of seminal plasma was negatively correlated with potassium and magnesium, whereas it was positively correlated with semen volume, sperm concentration and motility. The potassium content of seminal plasma was positively correlated with magnesyum, whereas it was negatively correlated with semen volume and sperm motility. The magnesium content of seminal plasma was negatively correlated with semen volume, sperm concentration and motility. The semen volume was negatively correlated with sperm concentration.
Keywords: bull; seminal plasma; calcium; magnesium; sodium; potassium